SME innovation process: comparison of service and manufacturing firms (2019)
The article seeks to provide an understanding of process innovation, an area of innovation research where there is less contribution in the literature. The understanding of alternative ways in which companies innovate both their products and services, and organize and evaluate the results of their innovative activities is the focus of this study. To this end, a qualitative and explorative methodology was designed, focused on Small and Medium Enterprises (SME) from the information technology sector (ITS). It was then compared with a previous study of SME manufacturing in the food sector, both of which are in Costa Rica. Comprehensive, face to face interviews were implemented, with SME owners or managers who have recently launched an innovative service. The Nvivo version 10 software was used to process the information. The investigation results allowed the identification of a series of common phases and elements in the SME studied, for the development of innovations. Also, the existence of a series of differences and similarities in the innovation processes of these ITS SME with manufacturing SME was detected.